Imaging of coronary atherosclerosis in various susceptible groups - Munnur, Ravi Kiran (Cardiovasc Diagn Ther, 2016)
Coronary artery disease (CAD) is the leading cause of death and disability worldwide. Atherosclerosis, which is the primary pathophysiologic mechanism for the development of plaque leading to CAD, is a multifactorial process resulting from a complex interplay between genetic susceptibility and various risk factors such as hypertension (HT), dyslipidaemia, diabetes mellitus (DM) and smoking. In addition, influences from other disease states such as chronic kidney disease (CKD), obesity and the metabolic syndrome as well as gender and ethnic diversity also contribute to the disease process. Insights from pathological observations and advances in cellular and molecular biology have helped us understand the process of plaque formation, progression and rupture leading to events. Several intravascular imaging techniques such as intravascular ultrasound (IVUS), Virtual histology IVUS (VH-IVUS) and optical coherence tomography (OCT) allow in vivo assessment of plaque burden, plaque morphology and response to therapy. In addition, non invasive assessment using coronary artery calcium (CAC) score allows risk stratification and plaque burden assessment whilst computed tomography coronary angiography (CTCA) allows evaluation of luminal stenosis, plaque characterisation and quantification. This review aims to summarise the results of invasive and non-invasive imaging studies of coronary atherosclerosis seen in various high-risk populations including DM, metabolic syndrome, obesity, CKD and, gender differences and ethnicity. Understanding the phenotype of plaques in various susceptible groups may allow potential development of personalised therapies.